Reducing Dispensing Time by Applying the Lean Hospital Approach in the Outpatient Pharmacy Department of SMC Telogorejo Hospital in Semarang Indonesia - Cicilia Tyasti Wahyunengsih; Titien Siwi Hartayu (Sanata Dharma University, 2025)
The outpatient pharmacy department is the last service unit visited by patients. One common concern is the delay in receiving medicine. Improvements in medicine dispensing time were made with a lean hospital. This study aims to analyze the impact of lean hospital interventions on waiting times and Value Added Ratio (VAR). This quasi-experiment was conducted with a non-equivalent control group before-after design. The study population included non-compounded medicine prescriptions with out-of-pocket healthcare from April to July 2024. The sample was 1,266 prescriptions. Direct observation gathered data for value stream mapping in non-compounded medicine dispensing, recording time for prescription screening, preparation, final checks, and delivery, including patient education. Activity time was considered value-added time. Value-added time divided by Cycle Time (CT) was used to calculate VAR. Critical waste identified by the root-cause analysis was conducted through in-depth interviews using the fishbone diagram guide. Data before and after intervention were analyzed using the Mann-Whitney U-test. Inventory waste significantly affected dispensing times. The lean hospital strategy improved the efficiency of pharmaceutical services by reducing the dispensing time from 19.68 to 16.18 minutes (p 0.001) and increasing the VAR from 51.34% to 57.21% (p 0.001) with an automated medicine planning system.